Anomalous 33S in the Lunar Mantle. Issue 2 (18th February 2023) - Dottin, J. W.; Kim, S.‐T.; Wing, B.; Farquhar, J.; Shearer, C.
Abstract: The origin, evolution, and cycling of volatiles on the Moon are established by processes such as the giant moon forming impact, degassing of the lunar magma ocean, degassing during surface eruptions, and lunar surface gardening events. These processes typically induce mass‐dependent stable isotope fractionations. Mass‐independent fractionation of stable isotopes has yet to be demonstrated during events that release large volumes of gas on the moon and establish transient lunar atmospheres. We present quadruple sulfur isotope compositions of orange and black glass beads from drive tube 74002/1. The sulfur isotope and concentration data collected on the orange and black glasses confirm a role for magmatic sulfur loss during eruption. The Δ 33 S value of the orange glasses is homogenous (Δ 33 S = −0.029‰ ± 0.004‰, 2SE) and different from the isotopic composition of lunar basalts (Δ 33 S = 0.002‰ ± 0.004‰, 2SE). We link the negative Δ 33 S composition of the orange glasses to an anomalous sulfur source in the lunar mantle. The nature of this anomalous sulfur source remains unknown and is either linked to (a) an impactor that delivered anomalous sulfur after late accretion, (b) sulfur that was photochemically processed early during lunar evolution and was transported to the lunar mantle, or (c) a primitive sulfur component that survived mantle mixing. The examined black glass preserves a mass‐dependent Δ 33 S composition (−0.008‰ ± 0.006‰, 2SE). The orange and black glasses are considered genetically related, but the discrepancy in Δ 33 S composition among the two samples calls their relationship into question. Plain Language Summary: Using isotopic compositions measured in volatile elements, we can identify the processes linked to isotopic fractionations and ultimately understand processes involved in a planets' evolution. We present sulfur isotope compositions of lunar glass beads from drive tube 74002/1 and demonstrate that an anomalous sulfur source was erupted from the lunar mantle with the orange glass beads. The observed isotopic anomaly has an unknown origin, but it requires a source of sulfur that was photochemically processed prior to its delivery to the lunar mantle and eruption at ∼3.6 Ga. Our results suggest that the lunar mantle is not well mixed with respect to sulfur sources and requires future multi‐disciplinary investigations to reconcile these important observations. Key Points: Orange glass 74002 preserves negative Δ 33 S values The negative Δ 33 S associated with orange glass is linked to photochemically processed sulfur in the erupted source Orange and black glass preserve different S isotope compositions that calls into question their genetic relationship